Space Aquaculture: Prospects for Raising Aquatic Vertebrates in a Bioregenerative Life-Support System on a Lunar Base - Przybyla, Cyrille (Frontiers in Astronomy and Space Sciences, 2021)
The presence of a human community on the Moon or on Mars for long-term residence would require setting up a production unit allowing partial or total food autonomy. One of the major objectives of a bioregenerative life-support system is to provide food sources for crewed missions using in situ resources and converting these into the food necessary to sustain life in space. The nutritive quality of aquatic organisms makes them prospective candidates to supplement the nutrients supplied by photosynthetic organisms already studied in the context of space missions. To this end, it is relevant to study the potential of fish to be the first vertebrate reared in the framework of space agriculture. This article investigates the prospects of space aquaculture through an overview of the principal space missions involving fish in low orbit and a detailed presentation of the results to date of the Lunar Hatch program, which is studying the possibility of space aquaculture. A promising avenue is recirculating aquaculture systems and integrated multi-trophic aquaculture, which recycles fish waste to convert it into food. In this sense, the development and application of space aquaculture shares the same objectives with sustainable aquaculture on Earth, and thus could indirectly participate in the preservation of our planet.